Egg chorion exploration of two important pests of family Noctuidae Latreille, 1809 from Himachal Pradesh (India) (Insecta: Lepidoptera) - Amritpal Singh Kaleka; Sainika Jallundhara; Yachana Kapoor (SHILAP)
Modern systematics uses taxonomy to reflect evolutionary history and in Lepidoptera, immature stage morphology is largely unknown for most species, but it has potential for classification and systematic studies as, Lepidoptera are common major and minor agricultural pests, the present study includes the examination of ultrastructure of Lepidoptera eggs of two pests, Agrotis ipsilon (Hufnagel, 1766) and Spodoptera litura (Fabricius, 1775) through scanning electron microscope (SEM), following a thorough investigation of the structural complexity of these tiny eggs, detailed ultrastructural descriptions, and comparative analyses, as well as identification keys, for important egg characters have been compiled, these findings will enrich the taxonomic database and update future pest management studies aimed at early potential pest detections at a much earlier stage of their life histories